2019
DOI: 10.1039/c9fo02032b
|View full text |Cite|
|
Sign up to set email alerts
|

Stevia residue extract increases intestinal uric acid excretionviainteractions with intestinal urate transporters in hyperuricemic mice

Abstract: The supplementation of STVRE significantly attenuated hyperuricemia and oxidative stress, upregulated ABCG2 and downregulated GLUT9 (protein and mRNA) expression in hyperuricemic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
6
28
0
Order By: Relevance
“…Besides, studies on monomeric compounds remain scarce, and in general, there is a lack of high-quality clinical research. For example, it has been shown that stevia residue extract can reduce SUA levels in HUA mice, and this was attributed to the presence of flavonoids [ 51 ], thereby indicating that the effects of flavonoids in the treatment of HUA require further study. The established hypouricemic effects and mechanisms of action of the bioactive components of flavonoids in plant-based functional foods are summarized in Table 2 and Table 3 , and the structures of flavonoids obtained from these plant-based functional foods are illustrated in Figure 3 .…”
Section: Bioactive Components Of Plant-based Functional Foodsmentioning
confidence: 99%
“…Besides, studies on monomeric compounds remain scarce, and in general, there is a lack of high-quality clinical research. For example, it has been shown that stevia residue extract can reduce SUA levels in HUA mice, and this was attributed to the presence of flavonoids [ 51 ], thereby indicating that the effects of flavonoids in the treatment of HUA require further study. The established hypouricemic effects and mechanisms of action of the bioactive components of flavonoids in plant-based functional foods are summarized in Table 2 and Table 3 , and the structures of flavonoids obtained from these plant-based functional foods are illustrated in Figure 3 .…”
Section: Bioactive Components Of Plant-based Functional Foodsmentioning
confidence: 99%
“…To attenuate hyperuricemia‐induced vascular endothelial injury, phloretin not only reduces the inflammatory factor expression and NF‐κB/ERK activation induced by uric acid but also blocks the cellular uptake of uric acid via inhibiting the expression of transporter proteins (Liu et al, 2017). Similar urate transporter‐blocking activities have also been observed for stevia residue extract attenuating hyperuricemia and oxidative stress, upregulating ABCG2, and downregulating GLUT9 (protein and mRNA) expression in hyperuricemic mice (Mehmood et al, 2019). in vivo study also has revealed that apple polyphenols extract exhibited protections on endothelium function, which is associated with reducing vascular oxidative stress, fasting plasma glucose, and uric acid (Cicero et al, 2017).…”
Section: The Mechanisms Of Polyohenols Improving Endothelial Dysfunctionmentioning
confidence: 52%
“…Previously, many authors reported the modulatory effect of fruits and vegetables extract on the ABCG2 expression in various animal models (Chen et al, 2019; Mehmood, Zhao, Wang, Hossen, Raka, et al, 2019; Mehmood, Zhao, Wang, Nadeem, et al, 2019; Qian et al, 2019; Wang et al, 2017). Recently, we observed that stevia residue extract attenuate hyperuricemia via upregulating ABCG2 transporter in small intestinal tissues in hyperuricemic mice (Mehmood, Zhao, Wang, Hossen, Raka, et al, 2019). Similarly, Wang et al (2017) also observed the decrease in the intestinal ABCG2 expression (model group) in fructose‐induced hyperuricemic rat which was upregulated by the administration of chicory extract.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemistry (IHC) analysis were performed according to the method of Wang, Lin, Zhang, Nie, and Bian (2017) and Mehmood, Zhao, Wang, Hossen, Raka, et al (2019). The intestinal tissues were deparaffinized from embedding in xylene and antigens were removed by treating with the sodium citrate buffer solution.…”
Section: Methodsmentioning
confidence: 99%